The Role of Religion in Building Peace in Southeast Asia: A Systematic Literature Review - Sidik, Mohamad Dindin Hamam; Dilawati, Rika (Parahyangan Catholic University, 2025)
This study aims to systematically examine the role of religion in peacebuilding in Southeast Asia, a region marked by significant religious and cultural diversity as well as recurring ethno-religious conflicts. While religion is often associated with violence, this research highlights its constructive potential by mapping how religious actors, institutions, and values contribute to reconciliation and social cohesion. Employing a qualitative Systematic Literature Review (SLR) approach, this study analyzed 35 peer-reviewed journal articles published between 2014 and 2024, selected from databases such as Scopus and Google Scholar. The articles were screened using inclusion and exclusion criteria focusing on empirical research dealing explicitly with religion and peace within Southeast Asia. The analysis identified five thematic areas: the role of religious actors, strategies of interfaith dialogue and mediation, integration of local wisdom, institutional and political challenges, and the contribution of religious education. The findings reveal that religious figures—across Islam, Buddhism, and Christianity—have been central in peacebuilding initiatives, particularly when supported by grassroots legitimacy and cultural contextualization. Dialogical approaches, cultural sensitivity, and educational programs emerged as effective mechanisms for fostering tolerance and reconciliation. However, structural challenges, such as state bureaucracy, ideological resistance, and illiberal policies, continue to hinder the full participation of religious actors in formal peace processes. The study underscores the importance of multi-level collaboration and the recognition of religious institutions not merely as symbolic agents, but as strategic partners in sustainable peacebuilding. Its originality lies in its comprehensive synthesis of literature that bridges fragmented local case studies into a regional framework, offering new insights for both academic discourse and policy development on religion and peace in Southeast Asia.